Exploring Lived Experiences and Perceptions of Teachers on Active Learning Strategies in Second Language Classrooms: A Phenomenological Study - Thapa , Deepak (Nepalese Linguistics, 2025)
Active learning has recently gained enormous attention in the field of language education. This paper critically explores teachers’ experiences and perceptions on ’active learning’. I employed interpretive hermeneutic phenomenological research method to explore the perception of three secondary-level English teachers (n=3), utilizing semi-structured interview questions. The study focused on how language teachers experience and perceive active learning strategies in their language classrooms. The findings of the study revealed that using active learning strategies in second language classrooms significantly fosters students’ engagement, autonomy and language proficiency, and promotes critical thinking skills. Furthermore, the study examined the inherent problems associated to active learning with the possible solutions. This study is significant because it offers practical teaching strategies of active learning to teachers and educators such as creative lectures, presentations, flipped-classroom model and translanguageing approaches to enhance learner-centered pedagogy in Nepalese unique English language teaching context.